How False Social Media Beauty Standards Lead To Body Dysmorphia - Hafeez, Erum; Zulfiqar, Fatima (Pakistan Journal of Humanities and Social Sciences, 2023)
Social media apps, owing to their technological advancements and applications of photo editing tools, have digitalized the female body and in doing so have led to the creation of unrealistic beauty ideals. Social media along with cultural factors created a socio-digital construct in which an attractive and successful woman embodies European features. Repeated exposure to this kind of imagery has made women feel uncomfortable in their bodies. Objectification of young women to such an extent has created an environment where an increasing number of women are suffering from body image issues, such as body dysmorphic disorder. A mental health condition, whereby people utilize most of their time worrying about perceived flaws in their appearance. The excess of this disorder can lead to poor self-esteem, self-harm, depression, and even suicide. It is most common in teens and young adults. This study investigates the patterns of toxic social media trends, how they are being integrated into society and why young women are falling prey to them. The research methodology comprised of a mixed-method approach. It was conducted in two stages: the first half consisted of a Google survey which was shared online with Facebook Female-centric groups besides Instagram and WhatsApp.In the second stage, in-depth interviews of eight women, belonging to different backgrounds offitness trainer, psychologist, feminist writer, model, nutritionist, and three students from the age groups of 18, 21, and 24 were sampled. The reason for opting mixed method was to strengthen the study and enhance its authenticity through in-depth interview analysis.